Dimensions of public debate on sexual violence against women: similarities and differences between Greece and EU policy framing - Hadjiyanni Αndromachi; Kamoutsi, Fray (The Greek Review of Social Research, 2016)
This article aims at a critical analysis of Greek public discourse concerning various forms of sexual violence, as presented mainly in Parliamentary discussions, but also in the press where politicians and activists debate the issue. Using the Mageeq methodology and analysed documents, the objective is to investigate the way in which various social actors define gender and make it apparent (or not) within the respective discourse, as well as to examine the framing of specific issues of sexual violence (intra-family violence and trafficking). An additional objective is to highlight the differences and similarities in the conceptualisation of these forms of sexual violence between EU policy texts and the Greek case.